Nutritive value and in vitro digestibility of yeast-fermented corn dust with cassava pulp affected by ensiling time - Lunsin, Ratchataporn; Pilajun, Ruangyote; Foiklang, Suban; Panatuk, Julakorn (วารสารแก่นเกษตร, 2021)
The aims of this study was to determine the chemical composition and nutritive value of yeast-fermented corn dust with cassava pulp using in vitro gas production technique. The experiment followed the completely randomized design with 6×5 factorial arrangement. Factor A comprised 6 ratios of fermented corn dust with cassava pulp (100:0, 80:20, 60:40, 40:60, 20:80, and 0:100% dry matter (DM), respectively), and factor B comprised 5 ensiling times (0, 5, 10, 15, and 20 days ensiled, respectively). Corn dust and cassava pulp were taken to treat with yeast solution according to the treatments and ensiled in a plastic bag at room temperature. The feed samples (200 mg dry matter from each) were incubated in vitro with rumen fluid taken from two male crossbred beef cattle (Thai-native x Charolais) at 2, 4, 6, 8, 12, 18, 24, 36, 48, 72, and 96 h. The results showed that increasing level of cassava pulp as a substrate fermented with corn dust decreased dry matter, crude protein, ether extract, neutral detergent fiber, and acid detergent fiber (P<0.01); whereas, organic matter and crude fiber were increased when increasing the level of cassava pulp (P<0.01). After 15 days ensiled, all treatments of yeast-fermented corn dust with cassava pulp showed greater chemical composition than other ensiling times. Moreover, gas kinetics, gas production, in vitro digestibility, and metabolizable energy content in yeast-fermented corn dust with cassava pulp at the ratio of 40:60, 20:80, and 0:100% DM on day 15 of ensiled were significantly greater than other treatments (P<0.01). Therefore, yeast-fermented corn dust with cassava pulp at the ratio of 40:60, 20:80, and 0:100% DM after 15 days ensiled could be an alternative animal feed resource for ruminants.